Image Processing Detecting Chili Fruit Based on Maturity Level Using Backpropagation Method - Agung Prayogi; Akim M.H Pardede; Katen Lumbanbatu (International Journal of Health Engineering and Technology, 2022)
Red chili is one type of vegetable that has a high economic value. Chili is usually used in the form of fresh or dried or cooked, for ingredients for kitchen spices, medicinal ingredients, the needs of the food industry, and home industries. . However, it is common for farmers to harvest red chilies that are not yet ripe or even ripe, such as reddish-brown, red-black (rotten). This can lead to a lack of maturity level of red chili and the quality of the red chili. From the input pattern/image of chili as training data and training targets, it is possible to identify the ripeness of chilies using the backpropagation method. Based on the image data of chilies, it can recognize the pattern of chilies that have a maturity level that is in accordance with the digital image by using the backpropagation method and using the MATLAB application, with an accuracy level of training and testing data that is 97,78%.